Processo de compartilhamento de conhecimento organizacional no TCE-PB à luz das teorias sociotécnica e de criação de conhecimento. - Souza, Aldacilene Sobreira de Medeiros (2007)
In the globalizated world, of intransigent competition and constant changes, the knowledge is considered an important activate organizational. For this reason, several organizations have been investing in linked strategies to the administration of the knowledge, especially in what it plays to the creation, storage and use of the knowledge socially elaborated. It is worth to point out, however, that the knowledge resides in the people's head and that, in the organizational context, your alone generation becomes possible starting from the interaction among the several organization actors. Like this, much more than the investment in equipments and computerized systems, an administration of the knowledge executes it requests the existence of a favorable atmosphere to the sharing of the knowledge. In this sense, the present study analyzed the process of sharing of the knowledge in the Tribunal de Contas do Estado da Paraíba to the light of the Theories of knowledge creation and sociotécnica. The approach used in this study it was quanti-qualitative and the research type was characterized as case study, with an exploratory and descriptive focus. The data were collected through questionnaires and agreements through the use of the statistical package SPSS and of the content analyses and documental. The study appeared that the sharing of the knowledge inside of the researched organization it happens not in way systematized and that, in spite of to the investments in technology of the information, they lack actions that make possible the creation of an appropriate context the constant creation of the Organizational knowledge. The pertinence of the beginnings of the Theory sociotécnica was also verified in relation to the precepts of the Theory of creation of the organizational knowledge, just depending on a adapted reading and necessary adjustment of such beginnings.